Extrusion processing of low-inhibitor soybeans improves growth performance of nursery pigs fed protein-adequate diets - A J Lewis; P G Reddy; D B Jones; M A Giesemann; Joe D Hancock (Kansas Agricultural Experiment Station Research Reports, 1991)
One hundred fifty weanling pigs (15.4 lb avg initial wt) were used in a 35-d growth assay to determine the effects of processing method (roasting in a Roast-A-Tron roaster vs extrusion in an Insta-Pro extruder) on nutritional value of soybeans with (+K) and without (-K) gene expression for the Kunitz trypsin inhibitor. Treatments were: 1) soybean meal with added soybean oil; 2) +K roasted; 3) +K extruded; 4) -K roasted; and 5) -K extruded. All diets were corn-based and formulated to 1.25% lysine for d 0 to 14 and 1.10% lysine for d 14 to 35 of the experiment. For d 0 to 14, 14 to 35, and 0 to 35, pigs fed extruded soybeans had improved ADG and F/G compared to pigs fed roasted soybeans. Digestibilities of DM, N, and gross energy were greater for diets with extruded soybeans than diets with roasted soybeans, and diets with soybean meal and soybean oil were intermediate. The response to extrusion processing was greater with -K than +K soybeans, with pigs fed extruded -K soybean having the greatest growth performance and nutrient digestibilities and lowest skinfold thickness of any treatment. Extrusion processing of +K and -K soybeans improved growth performance and nutrient digestibility in weanling pigs fed protein-adequate diets.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Soybeans; Process; Starter; Performance; Trypsin inhibitor; Immunology